2001
DOI: 10.1557/jmr.2001.0398
|View full text |Cite
|
Sign up to set email alerts
|

Study of the activation process of Mg-based hydrogen storage materials modified by graphite and other carbonaceous compounds

Abstract: A nanocomposite (Mg–V)nano made of 90 wt% Mg and 10 wt% V was prepared by high-energy ball-milling during 40 h. The activation characteristics of (Mg–V)nano are rather poor, the hydrogen content [H] reaching 4 wt% after more than 100 h (t4wt%) following the initial exposure of the material to H2. Adding 9 wt% graphite to (Mg–V)nano and resuming the milling operation for 30 min leads to the formation of (Mg–V)nano /G, which exhibits a t4wt% value of only 10 min. The addition of more than 9 wt% graphite to (Mg–V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 24 publications
4
57
0
Order By: Relevance
“…The activated carbons probably also played a role of dispersing agent and prevent oxidation of magnesium. This effect was proved in previous investigation from the authors [8] and in other published results in the literature [6,7,11,12]. In Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The activated carbons probably also played a role of dispersing agent and prevent oxidation of magnesium. This effect was proved in previous investigation from the authors [8] and in other published results in the literature [6,7,11,12]. In Fig.…”
Section: Resultssupporting
confidence: 85%
“…A large number of studies on composite materials based on magnesium with different additives, obtained by high-energy ball milling, were performed during the past years. It was established that some additives such as 3d metals, different oxides, some intermetallic compounds and carbon containing materials improve the hydrogen sorption properties of magnesium [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that carbon would favour a more efficient catalyst particle distribution. Moreover, recent studies have demonstrated that co-milling metal hydrides with carbon improves hydrogen sorption kinetics [10][11][12][13][14][15][16], suggesting that carbon plays a catalytic role. Zr 7 Ni 10 was chosen for the experiment, among the Zr x Ni y catalysts investigated in this work, because this particular composition is easier to activate, thus easier to turn into a fine powdery form.…”
Section: Samplementioning
confidence: 99%
“…The introduction of small amounts of additives (typically transition metals and transition metal oxides, but also carbons [6,7]) has also improved the kinetic rates of absorption and desorption significantly [8]. However, reducing the equilibrium temperature of desorption relies on lowering the thermodynamic enthalpy, and one of the more promising pathways for this is the formation of magnesium alloys with other metals.…”
Section: Introductionmentioning
confidence: 99%